Self-care practices and associated factors among hypertensive patients at public hospitals in North Shewa zone, Ethiopia - Kebede, Hailemelekot Bekele; Yosef, Tewodros; Bilchut, Awraris Hailu; Workie, Sewnet Getaye; Shifera, Nigusie; Mezgebu, Alemnew Destaw (Frontiers in Medicine, 2024)
Background Hypertension significantly contributes to premature mortality worldwide, highlighting the need for effective self-care to manage its complications. However, there is limited research on self-care practices among hypertensive patients in Ethiopia. This study assessed self-care practices and associated factors in hypertensive patients at public hospitals in North Shewa zone, Amhara Region, Ethiopia. Methods A hospital-based cross-sectional study was conducted with 450 participants using multi-stage sampling and interviewer-administered questionnaires. Data were processed with Epi-Data 4.6.0.6 and analyzed using SPSS 23. Descriptive statistics summarized the results, while bivariable and multivariable logistic regression identified factors associated with self-care practices. Crude and adjusted odds ratios with 95% confidence intervals were calculated, with significance at p < 0.05. Results Out of 450 participants, 231 (51.3, 95% CI: 46.4–55.6%) exhibited poor hypertension self-care practices. Factors associated with poor self-care included having a college-level education (AOR = 0.27, 95% CI: 0.07–0.95), university-level education (AOR = 0.36, 95% CI: 0.13–0.98), being widowed/widower (AOR = 5.30, 95% CI: 1.05–27.2), poor knowledge of hypertension (AOR = 4.51, 95% CI: 2.44–8.59), inadequate stress management (AOR = 3.10, 95% CI: 1.64–5.74), and first diagnosis during a check-up (AOR = 7.72, 95% CI: 4.22–13.8). Conclusion This study highlights inadequate self-care among hypertensive individuals, affected by factors such as education, marital status, knowledge, stress management, and diagnostic practices. Personalized interventions focusing on health education, stress management, and proactive screening are essential for improving health outcomes. Additionally, psychological support enhances emotional well-being and self-care engagement in hypertension patients, leading to better health outcomes and quality of life.